Design of Rental Flats with An Energy-Saving Architecture in Kendari City - Abdul Fattaah Mustafa (Jurnal RAUT, 2023)
The population growth in Kendari City has increased significantly every year from 2014-2020. This increase is not balanced with other infrastructure improvements so that the distribution of development is uneven which ultimately has implications for the growth of slum settlements, which are characterized by low quality of environmental sanitation, messy building layouts and other problems. An alternative to solving the need and the problem of land prices which has an impact on the difficulty of providing housing in urban areas is to build a residential model of flats with an emphasis on energy-efficient architecture. In planning, this study uses a quantitative descriptive approach. The results of the study show that energy savings can be applied to rental flats by maximizing natural lighting during the day by making openings in the form of voids and open sides of the stairs to let sunlight into the corridor area. In addition, it also aims to maximize natural ventilation so that the building becomes cooler.Keyword: Flats, Energy Efficient